Trends in Disease Burden Attributable to Tobacco in China, 1990–2017: Findings From the Global Burden of Disease Study 2017 - Wen, Haoyu; Xie, Cong; Wang, Fang; Wu, Yini; Yu, Chuanhua (Frontiers in Public Health, 2020)
In 2018, there were more than 371 million cigarette smokers and 12.6 million electronic cigarettes users, with 340.2 million non-smokers exposed to secondhand smoke (SHS) in China, which resulted in heavy tobacco-attributable disease burden. According to the definition by the Global Burden of Disease Study 2017 (GBD 2017), tobacco is a Level 2 risk factor that consists of three sublevel risk factors, namely, smoking, SHS, and chewing tobacco. In this study, we aim to evaluate the trends in deaths and disability-adjusted life years (DALYs) attributable to tobacco, smoking, SHS, and chewing tobacco by sex in China from 1990 to 2017 and explore the leading causes of tobacco-attributable deaths and DALYs using data from the GBD 2017. From 1990 to 2017, tobacco-attributable death rates per 100,000 people decreased from 75.65 (95% uncertainty interval, 56.23–97.74) to 70.90 (59.67–83.72) in female, and increased from 198.83 (181.39–217.47) to 292.39 (271.28–313.76) in male. From 1990 to 2017, tobacco-attributable DALY rates decreased from 2,209.11 (1,678.63–2,791.91) to 1489.05 (1,237.65–1,752.57) in female, and increased from 5,650.42 (5,070.06–6,264.39) to 6,994.02 (6,489.84–7,558.41) in male. In 2017, tobacco-attributable deaths in China were concentrated on chronic obstructive pulmonary disease, ischemic heart disease, lung cancer and stroke. The focus of tobacco control for female was SHS in 1990, whereas smoking and SHS were equally important to tobacco control in female in 2017. Increasing tobacco taxes and prices may be the most effective and feasible measure to reduce tobacco-attributable disease burdens.